Игрушка: стихи / А. Л. Барто ; худож. И. Есаулов - Барто Агния Львовна (Жили-были малыши, 2012)
Экземпляры: ф.8 (20131108) / Инвентарный номер: 55258 / Цена: / Сис.шифр: 84(2Рос-Рус)6-5 / Авт.знак: Б 24 / ГРНТИ: 17.82.93 / ББК: 84(2Рос-Рус)6-5